Propagation of registration errors into the change in maximum total point motion for determining stability of tibial baseplates. Issue 9 (11th August 2021) - Niesen, Abigail E.; Hull, Maury L.
Abstract: The change in maximum total point motion (ΔMTPM) is used to predict long-term risk of tibial baseplate loosening, however, effects of registration error on ΔMTPM have not been quantified for marker-based and model-based radiostereometric analysis (RSA). Registration errors for marker-based and model-based RSA were applied to a stable tibial baseplate in MATLAB simulations to determine the bias and precision in ΔMTPM and the proportions of baseplates which fell above the continuous migration stability limit. No bias error occurred, however, the precision of ΔMTPM was twice as large for model-based RSA than marker-based RSA, resulting in about 25% of stable baseplates falling above the continuous migration stability limit for model-based RSA. Reseachers should be aware of these limitations when applying this stability limit to assess tibial baseplate stability using model-based RSA.